A pooled analysis of continued prophylactic efficacy of quadrivalent human papillomavirus (types 6/11/16/18) vaccine against high-grade cervical and external genital lesions (2009)
Quadrivalent human papillomavirus (HPV) vaccine has been shown to provide protection from HPV 6/11/16/18-related cervical, vaginal, and vulvar disease through 3 years. We provide an update on the efficacy of the quadrivalent HPV vaccine against high-grade cervical, vaginal, and vulvar lesions based on end-of-study data from three clinical trials. Additionally, we stratify vaccine efficacy by several baseline characteristics, including age, smoking status, and Papanicolaou (Pap) test results. A total of 18,174 females ages 16 to 26 years were randomized and allocated into one of three clinical trials (protocols 007, 013, and 015). Vaccine or placebo was given at baseline, month 2, and month 6. Pap testing was conducted at regular intervals. Cervical and anogenital swabs were collected for HPV DNA testing. Examination for the presence of vulvar and vaginal lesions was also done. Endpoints included high-grade cervical, vulvar, or vaginal lesions (CIN 2/3, VIN 2/3, or ValN 2/3). Mean follow-up time was 42 months post dose 1. Vaccine efficacy against HPV 6/11/16/18-related high-grade cervical lesions in the per-protocol and intention-to-treat populations was 98.2% [95% confidence interval (95% CI), 93.3-99.8] and 51.5% (95% CI, 40.6-60.6), respectively. Vaccine efficacy against HPV 6/11/16/18-related high-grade vulvar and vaginal lesions in the per-protocol and intention-to-treat populations was 100.0% (95% CI, 82.6-100.0) and 79.0% (95% CI, 56.4-91.0), respectively. Efficacy in the intention-to-treat population tended to be lower in older women, women with more partners, and women with abnormal Pap test results. The efficacy of quadrivalent HPV vaccine against high-grade cervical and external anogenital neoplasia remains high through 42 months post vaccination. ©2009 American Association for Cancer Research.